Effect of Etching Time on Optical and Thermal Properties of p-Type Porous Silicon Prepared by Electrical Anodisation Method. (1st February 2012) - Behzad, Kasra; Mat Yunus, Wan Mahmood; Talib, Zainal Abidin; Zakaria, Azmi; Bahrami, Afarin; Shahriari, Esmaeil
Abstract : The porous silicon (PSi) layers were formed on p-type silicon (Si) wafer. The six samples were anodised electrically with 30 mA/cm 2 fixed current density for different etching times. The structural, optical, and thermal properties of porous silicon on silicon substrates were investigated by photoluminescence (PL), photoacoustic spectroscopy (PAS), and UV-Vis-NIR spectrophotometer. The thickness and porosity of the layers were measured using the gravimetric method. The band gap of the samples was measured through the photoluminescence (PL) peak and absorption spectra, then they were compared. It shows that band gap value increases by raising the porosity. Photoacoustic spectroscopy (PAS) was carried out for measuring the thermal diffusivity (TD) of the samples.